VITAMIN A - CHARACTERISTICS, STRUCTURE (Proceedings of Scientific Conference on Multidisciplinary Studies, 2024)
Vitamin A is a group of substances closely related in chemical structure, they are retinol (A1 vitamin A, axerophytol) and other retinoids with similar biological activity: dehydroretinol (vitamin A2), retinal (retinen, vitamin A1 aldehyde ) and retinoic acid. Provitamin A includes carotenoids, which are metabolic precursors of vitamin A; β-carotene is the most important among them. Retinoids are found in animal-derived foods, and carotenoids are found in plant-derived foods. All these substances are very soluble in non-polar organic solvents (for example, oils) and poorly soluble in water. Vitamin A is stored in the liver and can be accumulated in tissues. It is toxic in cases of overdose.